Evaluation of the role of sales promotion in influencing impluse buying behaviour: a comparison between international and local tourist at premium outlet in Malaysia - Syed Omar, Sharifah Faridah; Abdul Aziz, Yuhanis; Raja Yusof, Raja Nerina; Ng, Siew Imm (Global Academic Excellence, 2019)
The growing number of premium outlets in Malaysia has led to a new shopping experience to both local and international tourists. Associated with the concept of ‘everyday discount’, premium outlets would attract more consumers to purchase at the outlets. Previous studies have revealed the significant influence of sales promotion on consumer purchase behaviour as well as impulse buying behaviour. However, there are limited studies identifying the role of sales promotion on impulse buying behaviour in the perspective of international and local tourists. Moreover, previous research of literature on the premium outlets, especially in Malaysia are still lacking. Therefore this study aims to evaluate the role of sales promotion on impulse buying in the perspective of international and local tourists at premium outlets in Malaysia. Data were collected from 359 tourists at five premium outlets in Malaysia, using a self-administered questionnaire. The result of the study indicates that both groups have different preferences in terms of sales promotion that induced them to make an impulse purchase. This study suggests that retailers or marketers should improvise their pricing strategies and give out more samples and gifts to attract tourists to spend more money.